The Fables of Aesop : Selected, Told Anew, and Their History Traced - Aesop; Jacobs, Joseph, 1854-1916 (Salt Lake City, UT : Project Gutenberg, 1992)
"The Fables of Aesop" by Aesop is a collection of fables credited to a storyteller who lived in ancient Greece between 620 and 564 BCE. These short tales feature talking animals and plants that teach moral lessons through simple yet profound scenarios. Originally part of oral tradition, the stories were collected centuries after Aesop's death and have been continuously expanded, translated, and reinterpreted across cultures. The fables address ethical, social, and political themes, offering timeless wisdom through humble incidents that reveal great truths about human nature and behavior. (This is an automatically generated summary.)
The cock and the pearl -- The wolf and the lamb -- The dog and the shadow -- The lion's share -- The wolf and the crane -- The man and the serpent -- The town mouse and the country mouse -- The fox and the crow -- The sick lion -- The ass and the lapdog -- The lion and the mouse -- The swallow and the other birds -- The frogs desiring a king -- The mountains in labour -- The hares and the frogs -- The wolf and the kid -- The woodman and the serpent -- The bald man and the fly -- The fox and the stork -- The fox and the mask -- The jay and the peacock -- The frog and the ox -- Androcles -- The bat, the birds, and the beasts -- The hart and the hunter -- The serpent and the file -- The man and the wood -- The dog and the wolf -- The belly and the members -- The hart in the ox-stall -- The fox and the grapes -- The horse, hunter, and stag -- The peacock and Juno -- The fox and the lion -- The lion and the statue -- The ant and the grasshopper -- The tree and the reed -- The fox and the cat -- The wolf in sheep's clothing -- The dog in the manger -- The man and the wooden god -- The fisher -- The shepherd's boy -- The young thief and his mother -- The man and his two wives -- The nurse and the wolf -- The tortoise and the birds -- The two crabs -- The ass in the lion's skin -- The two fellows and the bear -- The two pots -- The four oxen and the lion -- The fisher and the little fish -- Avaricious and envious -- The crow and the pitcher -- The man and the satyr -- The goose with the golden eggs -- The labourer and the nightingale -- The fox, the cock, and the dog -- The wind and the sun -- Hercules and the waggoner -- The man, the boy, and the donkey -- The miser and his gold -- The fox and the mosquitoes -- The fox without a tail -- The one-eyed doe -- Belling the cat -- The hare and the tortoise -- The old man and death -- The hare with many friends -- The lion in love -- The bundle of sticks -- The lion, the fox, and the beasts -- The ass's brains -- The eagle and the arrow -- The milkmaid and her pail -- The cat-maiden -- The horse and the ass -- The trumpeter taken prisoner -- The buffoon and the countryman -- The old woman and the wine-jar -- The fox and the goat.
Wikipedia page about this book: https://en.wikipedia.org/wiki/Aesop%27s_Fables
Planned as PG's second Aesop extext. See also comprehensive versions PG#21 tr. by George Fyler Townsend, PG#11339 tr. by V. S. Vernon Jones, and illustrated PG#18732.
Release date is 1992-03-01
Keywords: Aesop's fables -- Adaptations; Fables, Greek -- Adaptations